Crop Management for Increasing Rice Yield and Nitrogen Use Efficiency in Northeast China. (1st September 2015) - Peng, Xianlong; Yang, Yanming; Yu, Cailian; Chen, Linan; Zhang, Mingcong; Liu, Zhilei; Sun, Yankun; Luo, Shenguo; Liu, Yuanyin
Abstract : Poor management is the main reason for high N losses and reduced yield in rice production. Improved crop management in northeastern China is becoming increasingly important due to economic pressures in southern and central China along with rising temperatures in the Northeast, which have led to a major shift in rice ( Oryza sativa L.) production to this region. Here, we examine the opportunities for improving the yield and nitrogen use efficiency (NUE) of irrigated rice in northeastern China by optimizing nutrients and increasing the transplanting density. In 2009 to 2011, field experiments were conducted to compare optimized nutrient management (ONM) and optimized crop management treatments (OCM) with the farmers' crop management (FCM) and no N treatment (control). Compared with the FCM, the ONM and OCM treatments significantly increased average grain yield by respective averages of 9 and 17%. These yield gains resulted from a combination of increases in grains per panicle and panicles per unit area. Compared with the FCM treatment, agronomic efficiency (AEN ), recovery efficiency of applied nitrogen (REN ) and partial factor productivity of applied nitrogen (PFPN ) were enhanced by an average of 120, 116, and 67% across the ONM and OCM treatments in the 3‐yr study period, respectively. It is clear that high yields combined with high N use efficiency are possible in northeastern China by appropriately increasing rice transplanting density and optimizing nutrient management.